EXPLORING THE CHALLENGES AND OPPORTUNITIES OF ARABIC LANGUAGE ACQUISITION AMONG 10TH GRADE STUDENT (A CASE STUDY AT RELIGIOUS PROGRAM OF MAN 1 BATAM) (PROCEEDING OF INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDY, 2025)
This study explores the challenges and opportunities in Arabic language acquisition among 10th-grade students in the Religious Program at MAN 1 Batam. Arabic, as a cornerstone of Islamic education, holds significant value for students in Indonesia, yet its complex grammar, distinct script, and limited real-life application present obstacles for non-native speakers. This research employs a qualitative case study approach, involving interviews, focus groups, and classroom observations with students and teachers to examine linguistic challenges, motivational factors, and institutional support in language learning. Findings reveal that grammar rules and vocabulary acquisition are major challenges for students, compounded by a lack of intrinsic motivation and limited exposure to Arabic outside the classroom. The study identifies traditional teaching methods as a potential barrier to engagement, suggesting that communicative, interactive approaches may enhance learning effectiveness. Extracurricular programs, such as language clubs, along with digital resources and culturally relevant content, are recommended to foster deeper engagement and practical language application. These insights provide valuable recommendations for improving Arabic language acquisition in religious educational settings, with an emphasis on enriching teaching strategies, expanding resource accessibility, and promoting extracurricular involvement